2018
DOI: 10.1080/20018525.2018.1506235
|View full text |Cite
|
Sign up to set email alerts
|

Lack of awareness towards smoking-related health risks, symptoms related to COPD, and attitudinal factors concerning smoking: an Internet-based survey conducted in a random sample of the Danish general population

Abstract: Background: Although chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality globally, several studies have shown little awareness of COPD in the general population. The awareness of COPD in the Scandinavian countries is, however, sparsely investigated. Objective: The aim of this study was to explore the awareness in the general Danish population of smoking-related health risks and symptoms related to COPD and attitudinal factors concerning smoking. Design: Adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, this is the first report highlighting that the topic "chronic obstructive pulmonary disease" is under-represented in Google search queries compared with other frequent but less preventable diseases. Accordingly, low awareness of COPD in the general population has been reported previously [13][14][15]. A recent investigation by SEO et al [16] assessed awareness and understanding of COPD in smokers participating in a smoking cessation programme.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report highlighting that the topic "chronic obstructive pulmonary disease" is under-represented in Google search queries compared with other frequent but less preventable diseases. Accordingly, low awareness of COPD in the general population has been reported previously [13][14][15]. A recent investigation by SEO et al [16] assessed awareness and understanding of COPD in smokers participating in a smoking cessation programme.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to our observation, S ikjær et al . [24] found that significantly fewer women than men had undergone pulmonary function testing, based on an Internet-based questionnaire administered to a random sample of the Danish population. The lower use of spirometry to measure and monitor lung function may be due to either provider or patient behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy awareness about risks of smoking in general, and the risk between shisha and tuberculosis [12], was important factor in our study and has a signi cance (p=0.041) which is so closed to the study [13] This study suggests weight as a risk factor for smoking. More weight, more smoke.…”
Section: Discussionmentioning
confidence: 62%